An effective solution to the optimal power flow problem using meta-heuristic algorithms - Aurangzeb, Khursheed; Shafiq, Sundas; Alhussein, Musaed; Pamir; Javaid, Nadeem; Imran, Muhammad (Frontiers in Energy Research, 2023)
Financial loss in the power systems is an emerging problem that needs to be resolved.To tackle the mentioned problem, the energy generated from various generation sources in the power network needs proper scheduling. In order to determine the best settings for the control variables, this study formulates and solves an optimal power flow (OPF) problem. In the proposed work, bird swarm algorithm (BSA), JAYA, and a hybrid of both algorithms, termed as HJBSA, are used for obtaining the optimum variables' settings. We perform simulations by considering the constraints of voltage stability and line capacity, and generated reactive and active power. Also, the used algorithms solve the problem of OPF as well as minimize carbon emission generated from thermal systems, fuel cost, voltage deviations and losses in generation of active power. The suggested approach is evaluated by putting it into use on two separate IEEE testing systems, one with 30 buses and the other with 57 buses. The simulation results show that for 30 bus system, the